-4(1+k)=-3-3k

Simple and best practice solution for -4(1+k)=-3-3k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(1+k)=-3-3k equation:


Simplifying
-4(1 + k) = -3 + -3k
(1 * -4 + k * -4) = -3 + -3k
(-4 + -4k) = -3 + -3k

Solving
-4 + -4k = -3 + -3k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '3k' to each side of the equation.
-4 + -4k + 3k = -3 + -3k + 3k

Combine like terms: -4k + 3k = -1k
-4 + -1k = -3 + -3k + 3k

Combine like terms: -3k + 3k = 0
-4 + -1k = -3 + 0
-4 + -1k = -3

Add '4' to each side of the equation.
-4 + 4 + -1k = -3 + 4

Combine like terms: -4 + 4 = 0
0 + -1k = -3 + 4
-1k = -3 + 4

Combine like terms: -3 + 4 = 1
-1k = 1

Divide each side by '-1'.
k = -1

Simplifying
k = -1

See similar equations:

| (3y^2-8y+1)-(2y^2-8y+8)= | | -37-x=35-9x | | -3r-12=4-r | | x-7/6=2 | | X*4=100 | | 10n+5-8n-3=12 | | 2(m+3)= | | 9-5/8x=10 | | 12-15x(-5)= | | x^2+22x=-84+10x | | 7n+29=8 | | -12x^3+9x^2=0 | | -26+4= | | -4=a-10u | | 8+x=-(x+8) | | -5-10x^2=-68 | | G=3j+4 | | y=7(-8)-26 | | -5+48= | | 16-3n=1-8n | | y=-5(-8)-35 | | (2z-7)(6+z)=0 | | y=3(-8)-72 | | 0.6t=0.9+0.4t | | 3(4z-7)=21+12z | | h/2=13.44 | | 7x/7=x | | 2(10*2)-4(5*2)= | | y=-8+92 | | 31-(2x+4)=2(x+6)+x | | n-4-2n=n+6-8+10 | | 83-2x=66 |

Equations solver categories